2019
DOI: 10.2131/jts.44.113
|View full text |Cite
|
Sign up to set email alerts
|

Bis(1,4-dihydro-2-methyl-1-phenyl-4-thioxo-3-pyridiolato)zinc(II) exhibits strong cytotoxicity and a high intracellular accumulation in cultured vascular endothelial cells

Abstract: Although cytotoxicity of inorganic metals has been well investigated, little is known about the cytotoxicity of organic-inorganic hybrid molecules. The cytotoxicity of zinc complexes was evaluated using a culture system of vascular endothelial cells. We found that bis(1,4-dihydro-2-methyl-1-phenyl-4-thioxo-3-pyridiolato)zinc(II), termed Zn-06, exhibited strong cytotoxicity in vascular smooth muscle cells, epithelial cells, fibroblastic cells, and vascular endothelial cells. This study showed that the tetracoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…We characterized the cytotoxicity of the hybrid molecules and applied this strategy to studies of intracellular signaling pathways that mediate regulation of vascular endothelial cell functions. Organic-inorganic hybrid molecules exhibit unique cytotoxicity in vascular endothelial cells [14][15][16][17][18]. Specifically, the cytotoxicity of organic-inorganic hybrid molecules is not simply dependent on their hydrophobicity, intracellular accumulation, molecular structures, or the intramolecular metals they contain.…”
Section: Introductionmentioning
confidence: 99%
“…We characterized the cytotoxicity of the hybrid molecules and applied this strategy to studies of intracellular signaling pathways that mediate regulation of vascular endothelial cell functions. Organic-inorganic hybrid molecules exhibit unique cytotoxicity in vascular endothelial cells [14][15][16][17][18]. Specifically, the cytotoxicity of organic-inorganic hybrid molecules is not simply dependent on their hydrophobicity, intracellular accumulation, molecular structures, or the intramolecular metals they contain.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that organic-inorganic hybrid molecules can accumulate within vascular endothelial cells independently of the hydrophobicity. Our research group has previously reported the cytotoxicity of organic-inorganic hybrid molecules in vascular endothelial cells (Murakami et al, 2015;Kohri et al, 2015;Hara et al, 2016Hara et al, , 2018bFujie et al, 2019b). These reports indicate that, in general, organic-inorganic hybrid molecules that easily accumulate within the cells exhibit strong cytotoxicity.…”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, we have previously reported that the cytotoxicity of organic-inorganic hybrid molecules is independent of the cytotoxicity of either the ligand alone or the intramolecular metal in its inorganic form. 18,22,23,[29][30][31][32] Activation of the NF-E2-related factor-2 by organic-inorganic hybrid molecules depends on the type of the coordinated metal ion. 33 Thus, it seems that the biological activities of organic-inorganic hybrid molecules depend on the interaction between the ligand structure and the intramolecular metal.…”
Section: Discussionmentioning
confidence: 99%
“…As the results obtained using this method are consistent with morphological evaluation of cells, this kit has been widely used for cytotoxicity assays. 18,[20][21][22][23] Furthermore, we assessed the cytotoxicity of Zn-12 by morphological observations and by evaluating lactate dehydrogenase leakage, in this study.…”
Section: Nonspecic Cell Damagementioning
confidence: 99%